2017
DOI: 10.1097/md.0000000000007328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of 3 treatments for patients with osteoporotic vertebral compression fractures

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Previously, a number of studies have explored the clinical efficacy and costs of PVP/PKP in China based on hospital data. Evidence showed that PVP/PKP can effectively relieve fracture-related pain, and PVP/PKP is considered as the best choice for OVCF [1,[15][16][17]. Nevertheless, regardless of OVCF intervention modality, PVP/PKP surgery is very expensive and can impose a heavy financial burden on patients.…”
Section: Osteoporotic Vertebral Compression Fractures (Ovcf)mentioning
confidence: 99%
“…Previously, a number of studies have explored the clinical efficacy and costs of PVP/PKP in China based on hospital data. Evidence showed that PVP/PKP can effectively relieve fracture-related pain, and PVP/PKP is considered as the best choice for OVCF [1,[15][16][17]. Nevertheless, regardless of OVCF intervention modality, PVP/PKP surgery is very expensive and can impose a heavy financial burden on patients.…”
Section: Osteoporotic Vertebral Compression Fractures (Ovcf)mentioning
confidence: 99%
“…Six RCTs included patients with less than 8 weeks of symptoms. 22,24,[28][29][30][31]32 Six studies included patients with more than 8 weeks and up to 12 months of symptoms. 6,7,23,[25][26][27] Six of the 12 RCTs did not specify the baseline pain score as their inclusion criteria.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 99%
“…Multiple reviews have assessed the efficacy of vertebroplasty for the treatment of back pain from osteoporotic VCF in RCTs, 12,32,[34][35][36][37][38][39][40][41][42][43] with some of them including non-RCTs. [35][36][37] These reviews showed the efficacy of vertebroplasty in improvement of pain compared to conservative management, but a systematic review of poorly designed cohort studies and non-RCTs generates only low quality of evidence in favour of vertebroplasty.…”
Section: How Is This Different From Other Reviews?mentioning
confidence: 99%
See 2 more Smart Citations